Electricity and electronics for renewable energy technology an introduction - Hemami, A. (Power electronics and applications series, 2016)
Electricity and Electronics for Renewable Energy Technology: An Introduction provides a foundational understanding of electricity and the methods and devices specific to electricity from renewable sources.